Resistance to ciprofloxacin in pathogenic Enterobacteriaceae in England and Wales in 1996. Issue 12 (December 1997) - Threlfall, E J; Graham, A; Cheasty, T; Ward, L R; Rowe, B
Abstract : In 1996, 6% of Escherichia coli from extraintestinal infections were resistant to ciprofloxacin with minimum inhibitory concentrations (MICs) > or = 2 mg/l (high level resistance). Low level resistance (MIC 0.125-1 mg/l) was also identified in 7% of Salmonella typhi, 4% of S paratyphi A, and 4% of non-typhoidal salmonellas. However, resistance to ciprofloxacin was rarely identified in shigellas. For E coli, physicians should be aware that treatment failures may occur when patients with invasive illness are treated with ciprofloxacin before the results of laboratory sensitivity tests are available. For salmonellas an increasing number of treatment failures have been recorded for patients infected with strains with low level resistance. Because of the increasing incidence of Enterobacteriaceae with low level resistance to ciprofloxacin, it is recommended that for this group of organisms a breakpoint of 0.125 mg/l should be included in laboratory sensitivity tests.